Advice, authority and autonomy in shared decision-making in antenatal screening: the importance of context - Pilnick, Alison; Zayts, Olga (Blackwell Publishing, 2016)
Shared decision making has been widely advocated across many branches of healthcare, yet there is considerable debate over both its practical application and how it should be examined or assessed. More recent discussions of SDM have highlighted the important of context, both internal and external to the consultation, with a recognition that decisions cannot be understood in isolation. This paper uses conversation analysis (CA) to examine how decision making is enacted in the context of antenatal screening consultations in Hong Kong. Building on previous CA work (Collins et al 2005; Toerien et al 2013), we show that, whilst previously identified formats are used here to present the need for a decision, the overriding basis professionals suggest for actually making a decision in this context is the level of worry or concern a pregnant woman holds about potential fetal abnormality. Professionals take an unknowing ‘epistemic stance’ (Heritage 2012) towards this worry, and hence step back from involvement in decision making. We argue that this is linked to the non-directive ethos that prevails in antenatal screening services, and suggest that more research is needed to understand how the enactment of SDM is affected by wider professional contexts and parameters.